Design and study of a combining energy harvesting system based on thermoelectric and flapping triboelectric nanogenerator. Issue 12 (26th September 2021) - Liu, Changxin; Zhao, Cong; Liu, Jianhao; Wang, Jianye; Wang, Yan; Fan, Yuhang; Zhao, Kaiyuan; Shan, Baichuan; Qu, Zhiyu; Ma, Kefei; Xu, Minyi; Pan, Xinxiang
ABSTRACT: In this paper, anew hybrid energy converter is designed which consists of a Thermoelectric Generator (TEG) unit and aTriboelectric Nanogenerator (TENG) unit. The device can harvest solar energy and wind energy from the environment individually or simultaneously, and utilize them as the energy source of sensors and wireless transmission equipment in the system. When working individually, the TENG unit can achieve 244 V output voltage and 35 Aoutput current from wind energy of 12m/s. The output voltage of 4.27 V and the output current of 328 mA can be obtained from the solar thermoelectric unit at the hot end temperature of 110°C. According to the experimental data of capacitor charging by hybrid energy converter, compared with TEG unit and TENG unit individually, the charging voltage of the proposed device increases by 93.3% and 28.9%, respectively, and successfully drives Bluetooth module and realizes wireless data transmission. Compared with the traditional method, the proposed unit achieves not only hybrid energy harvesting but also better output performance. It is an important exploration for the development of self-powered sensors in the future intelligent Internet of things.